Discourse markers in narrative, descriptive and expository writing of form 2 students / Noradzlina Adzhar - Adzhar, Noradzlina (2014)
This study was carried out with the aim to find out the usage of discourse markers (DMs) in writing both from the Form 2 students production and teachers' perception. A mixed method approach was used in this study. A quantitative approach was employed to investigate the usage of discourse markers which appear more frequently in the writings, and the types of discourse markers the respondents used the most. A qualitative approach was used to understand teachers’ perceptions, knowledge, and experiences related to the usage of DMs. The results of the study showed that elaborative discourse markers have been the most frequently used in all types of writings (narrative writing, descriptive writing and expository writing). The qualitative findings showed that, teachers perceived the use of discourse markers in students’ writing has pedagogical value, and presented as one of the writing skills. The main implication of this study emphasized on inculcating varieties of discourse markers in classroom practice. The findings showed students more focus on elaborative markers therefore, other cohesive devises need to be highlighted to improve the quality of the writing.